Sequence Variation Within the Fragile X Locus - Mathews, Debra J.; Kashuk, Carl; Brightwell, Gale; Eichler, Evan E.; Chakravarti, Aravinda (Genome Research, 2001)
The human genome provides a reference sequence, which is a template for resequencing studies that aim to discover and interpret the record of common ancestry that exists in extant genomes. To understand the nature and pattern of variation and linkage disequilibrium comprising this history, we present a study of ∼31 kb spanning an ∼70 kb region of FMR1, sequenced in a sample of 20 humans (worldwide sample) and four great apes (chimp, bonobo, and gorilla). Twenty-five polymorphic sites and two insertion/deletions, distributed in 11 unique haplotypes, were identified among humans. Africans are the only geographic group that do not share any haplotypes with other groups. Parsimony analysis reveals two main clades and suggests that the four major human geographic groups are distributed throughout the phylogenetic tree and within each major clade. An African sample appears to be most closely related to the common ancestor shared with the three other geographic groups. Nucleotide diversity, π, for this sample is 2.63 ± 6.28 × 10−4. The mutation rate, μ, is 6.48 × 10−10 per base pair per year, giving an ancestral population size of ∼6200 and a time to the most recent common ancestor of ∼320,000 ± 72,000 per base pair per year. Linkage disequilibrium (LD) at the FMR1 locus, evaluated by conventional LD analysis and by the length of segment shared between any two chromosomes, is extensive across the region.